Investigation of some peculiarities in internet advertising - Khakhaieva, M. E. (ТДАТУ, 2020)
Nowadays, more and more people use the Internet as the first source of obtaining the necessary information. Accordingly, the number of advertisements is also growing. But regardless of what kind of advertising is, for example, contextual advertising, frame advertising, pop-up banners, trick banners, contextual Internet advertising in search engines (SEA), product placement in Internet games or direct advertising, there is a main requirement for it - not to violate the law. Otherwise, if you go against these rules, the antimonopoly service can fine the company for a fairly large amount, and advertising will be banned from showing. It is also necessary to take into account the fact that officials learn about “prohibited” advertising mainly from competitors.
Keywords: advertisement; Internet advertising; requirements that advertising